Employees' attitude towards job and job performance the case of Land Bank and Metrobank employees - Caro, Catherine Aga; Catalan, Jo-am Begalan; Pagulayan, Annaleth Labrador; Plameras, Revo Yasay
Employees' attitudes toward their work are one very important factor in the success of an organization. This would be seen in their work performance. An employee who values his work so much tends to give his very best in whatever task assigned to him thus a better output for him as well as to the whole organization's performance. Employee's job performance could be seen in their attendance, mutuality, work relationship and co-employee relationship and work productivity. With this in mind the researchers thereforee chose to investigate whether employees' attitude towards their job affects job performance. To attest to this claim, the researchers conducted a survey on the employees of the two banks in Iloilo City specifically Landbank-Libertad Branch and Metrobank-General Luna Branch. Key variables that were considered were the employees' outlook towards job, their sense of belonging to the organization, perception of salary rate and other benefits, reaction to management style, attendance and work relationship. Based on the findings the researchers found out that all employees like their job for the fulfillment they get and the compensation and benefits they were able to obtain. Moreover, all respondents have a strong sense of belonging to their respective organization and they're comfortable with the management style being employed by their supervisors. The positive mind-set of employees towards their tasks and job assignments encourage them to perform their job well.